'Grenfell changes everything?' Activism beyond hope and despair. Issue 3 (27th May 2021) - Cornish, Flora
ABSTRACT: The horror of the devastating Grenfell Tower fire, and the shock that 'it could happen here', in 21st century Britain, led politicians, professionals, and community workers to proclaim that 'Grenfell changes everything'. Affected people, turned into activists by the disaster, committed to ensuring that such a disaster could never happen again, by demanding changes to regulations and policy. Whereas public health literature addressing activism focuses on strategies and conditions for 'successful' collective action, the experience of activism after Grenfell has been characterised by frustrating partial wins, inertia, delay, and setback. This paper seeks to theorise the activist condition of seeking change that is refused and to do so in a way that values the agency and care of (thwarted) activism. Inspired by Haraway's 'staying with the trouble' and critical scholarship on hope, and drawing on three years of knowledge exchange and ethnographic engagement with the community response after Grenfell, I explore the trajectories of six activist change efforts: a fire safety campaign, engagements with a Public Inquiry, campaigns to preserve community assets, community gardening, silent walks, and provision of support to children at a community centre, each addressing social determinants of health and 'staying with the trouble' in different ways. I argue that setbacks do not invalidate a struggle or warrant despair, but that in insisting on caring for others' lives, activism succeeds in instantiating a caring world. Beyond hope and despair is the staying power of communities who value human life and solidarity and keep fighting for them.